2009
DOI: 10.1007/s00198-009-1054-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing interest in an osteoporosis website: a survey among women eligible for osteoporosis screening

Abstract: These data suggest that middle-aged women are moderately receptive to the concept of web-based care for certain components of osteoporosis management and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…More than half of the pregnant women in this survey had interest in using the Internet for healthrelated information. This results are in line with the results of the previous researches (18,19,21,25,28,32,35,36). Access to information, demographics characteristics and, particularly, motivational factors all can influence patients' interest for using the Internet as a health information resource (28).…”
Section: Resultssupporting
confidence: 90%
“…More than half of the pregnant women in this survey had interest in using the Internet for healthrelated information. This results are in line with the results of the previous researches (18,19,21,25,28,32,35,36). Access to information, demographics characteristics and, particularly, motivational factors all can influence patients' interest for using the Internet as a health information resource (28).…”
Section: Resultssupporting
confidence: 90%
“…Women commonly use the Internet as a source for osteoporosis and other health information, 44,45 but websites often fail to provide adequate information. [31][32][33][34][35] Since the inception of this project, use of Internet-based risk assessments such as the FRAX-WHO risk assessment tool (http://www.shef.ac.uk/FRAX), which does not require BMD testing and can be self-administered, have become more prevalent.…”
mentioning
confidence: 99%
“…Nearly 30% of our population reported receiving education from sources such as TV, magazines, newspapers, books, pamphlets, friends, family, and the internet. Rozenfeld et al 14 demonstrated the impact of the media on health information in a 2006 survey of 3,000 female patients ages 50 to 85 (with a response rate of 26%) and found that 70% of survey respondents admitted to being somewhat or very likely to use the internet to gain knowledge about health-related issues. Furthermore, two-thirds of respondents said they would be likely to read about osteoporosis on a physician-prescribed osteoporosis management web site if one were to be developed.…”
Section: Discussionmentioning
confidence: 99%